COVID-19 cross-border case and contact tracing activities - experiences and lessons learnt, Germany, April-December 2020 - Ida Sperle; Uwe Koppe; Raskit Lachmann; Robert Vonderwolke; Nadine Püschel; Nadine Litzba; Paula Böhm; Janina Stauke; Annika Heck; Jonathan H.J. Baum; Luam Ghebreghiorghis; Gyde Steffen; et al. (BMC, 2023)
Abstract Background Interruption of transmission chains has been crucial in the COVID-19 response. The Emergency Operations Centre (EOC) at the Robert Koch Institute (RKI) coordinated cross-border case and contact tracing activities at the national level by sharing data with German public health authorities (PHA) and other countries. Data on these activities were not collected in the national surveillance system, and thus were challenging to quantify. Our aim was to describe cross-border COVID-19 case and contact tracing activities including lessons learnt by PHA to adapt the procedures accordingly. Methods Case and contact tracing events were recorded using unique identifiers. We collected data on cases, contacts, dates of exposure and/or SARS-CoV-2 positive test results and exposure setting. We performed descriptive analyses of events from 06.04.-31.12.2020. We conducted interviews with PHA to understand experiences and lessons learnt, applying a thematic approach for qualitative analysis. Results From 06.04.-31.12.2020 data on 7,527 cross-border COVID-19 case and contact tracing activities were collected. Germany initiated communication 5,200 times, and other countries 2,327 times. Communication from other countries was most frequently initiated by Austria (n = 1,184, 50.9%), Switzerland (n = 338, 14.5%), and the Netherlands (n = 168, 7.2%). Overall, 3,719 events (49.4%) included information on 5,757 cases (median 1, range: 1-42), and 4,114 events (54.7%) included information on 13,737 contacts (median: 1, range: 1-1,872). The setting of exposure was communicated for 2,247 of the events (54.6%), and most frequently included private gatherings (35.2%), flights (24.1%) and work-related meetings (20.3%). The median time delay between exposure date and contact information receipt at RKI was five days. Delay between positive test result and case information receipt was three days. Main challenges identified through five interviews were missing data or delayed accessibility particularly from flights, and lack of clear and easy to use communication channels. More and better trained staff were mentioned as ideas for improving future pandemic response preparedness. Conclusion Cross-border case and contact tracing data can supplement routine surveillance but are challenging to measure. We need improved systems for cross-border event management, by improving training and communication channels, that will help strengthen monitoring activities to better guide public health decision-making and secure a good future pandemic response.